2022
DOI: 10.3389/fimmu.2022.861290
|View full text |Cite
|
Sign up to set email alerts
|

Glycometabolism Reprogramming of Glial Cells in Central Nervous System: Novel Target for Neuropathic Pain

Abstract: Neuropathic pain is characterized by hyperalgesia and allodynia. Inflammatory response is conducive to tissue recovery upon nerve injury, but persistent and exaggerated inflammation is detrimental and participates in neuropathic pain. Synaptic transmission in the nociceptive pathway, and particularly the balance between facilitation and inhibition, could be affected by inflammation, which in turn is regulated by glial cells. Importantly, glycometabolism exerts a vital role in the inflammatory process. Glycomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 112 publications
0
8
0
Order By: Relevance
“…These alterations induced a diverse range of effects on the cells in that environment, such as facilitating the conversion of inflammatory phenotypes ( 38 ) and triggering oxidative stress ( 39 ). Recent studies showed that metabolic abnormalities could occur in this microenvironment ( 40 ), which theoretically could modify neuropathic pain if rectified ( 41 ). Interestingly, metabolic abnormalities could also exist in T cells.…”
Section: T-cell Energy Metabolism In Neuropathic Painmentioning
confidence: 99%
See 3 more Smart Citations
“…These alterations induced a diverse range of effects on the cells in that environment, such as facilitating the conversion of inflammatory phenotypes ( 38 ) and triggering oxidative stress ( 39 ). Recent studies showed that metabolic abnormalities could occur in this microenvironment ( 40 ), which theoretically could modify neuropathic pain if rectified ( 41 ). Interestingly, metabolic abnormalities could also exist in T cells.…”
Section: T-cell Energy Metabolism In Neuropathic Painmentioning
confidence: 99%
“…The enhancement of glucose metabolism implies that there might be a temporary decrease in glucose within the microenvironment. These metabolic alterations result in the accumulation of various intermediates, including phosphoenolpyruvate (PEP) ( 41 , 49 ) and lactate ( 41 , 49 , 50 ), which subsequently disturb the acid-base equilibrium in the microenvironment, driving a cascade of pathophysiological processes ( 41 ). Of note, astrocytes can produce L-lactate through the astrocyte-neuron lactate shuttle (ANLS), playing a crucial role in maintaining synaptic transmission ( 51 , 52 ).…”
Section: T-cell Energy Metabolism In Neuropathic Painmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies focused on the key influences of abnormal glycometabolism in neurons and supporting cells induced by chronic nerve injury. As is generally understood, energy metabolism is the core process in providing energy and substrates for signal transmission and cell responses, and glycolysis is the basis activity of cell energy metabolism 5 . Microglia are widely present in central nervous system and involved in various neurophysiological processes including neuronal development, synaptic remodelling and immune response.…”
Section: Introductionmentioning
confidence: 99%